10.3% Efficient CuIn(S, Se)2 Solar Cells from DMF Molecular Solution with the Absorber Selenized under High Argon Pressure. Issue 6 (30th March 2018) - Jiang, Jingjing; Yu, Shaotang; Gong, Yuancai; Yan, Weibo; Zhang, Rui; Liu, Shujuan; Huang, Wei; Xin, Hao
Abstract : Fabricating high performing chalcopyrite absorber material from environmental benign solvent is very important for large scale manufacturing production. Here, N, N‐dimethylformamide (DMF) is used as a single solvent to make CuIn(S, Se)2 (CIS) molecular precursor solution and fabricate CIS absorber material. A power conversion efficiency of 10.3% has been achieved from film selenized under 1.6 atmosphere Ar pressure which is 0% for film selenized under 1 atmosphere pressure. Characterizations using XRD, SEM, TEM, EDX reveal a Cu‐rich absorber material consisting of loosely connected grains with vertical holes in film selenized under 1 atmosphere and a Cu‐poor compact large‐grain top layer with large hole bottom layer in film selenized under high Ar pressure. Further optimization of precursor formulation and device fabrication conditions to address the non‐perfect double layer structure is expected to further improve DMF solution processed CIS solar cell efficiency. Our results demonstrate annealing precursor film under increased atmosphere pressure is a new and promising strategy to fabricate high performing thin film solar cells, which can be applied to all solution processed chalcogenide solar cells including CIS, CIGS and CZTS. Abstract : Highly efficient CuIn(S, Se)2 solar cells are demonstrated from DMF molecular precursor solution without KCN etching. Selenizing precursor film under 0.16 MPa Ar pressure converts a Cu‐rich CIS absorber with loose grains to a Cu‐poor dense‐grain material with 10.3% efficiency. High pressure selenization is a new and promising strategy to achieve high performing solution processed chalcogenide thin film solar cells.